Pembangunan Spiritualitas Anak Oleh Orang Tua Perspektif QS Maryam Ayat 30-32 - Mushaffa, Arju; Azmi, M. Ulul; Islam, Muhammad Thoriqul; Ludviana, Vieke; Amelia, Fatma; Fasya, Zaini; Noorhidayati, Salamah (LP2M Universitas Islam Ahmad Dahlan, 2025)
As a Muslims, the implementation of the educational process should be understood as an effort to convey, transform, and internalize the values of Islamic teachings, which cannot be separated from the teachings contained in the Qur'an and Hadith. This includes values that are closely related to the development of children's spirituality as an important part of character building. The purpose of this paper is to describe the development of children's spirituality by parents in Surah Maryam verses 30-32. As well as analyzing the values of spiritual education contained in Surah Maryam verses 30-32. The method used in this writing is the literature research method, where the author relies on various literatures to obtain research data. The purpose of this research is to find out the aspects of building children's spirituality by parents contained in QS Maryam verses 30-32. QS Maryam verses 30-32 contains three aspects of building children's spirituality by parents, namely aspects of Aqidah or faith, aspects of Shari'a or worship, and aspects of morality.